Dynamic Active Earth Pressures of the Retaining Piles with Anchors under Vehicle Loads - Hong-zhi Qiu; Ji-ming Kong; Ren-chao Wang (Shock and Vibration)
The pile-anchor supporting structure is widely used in foundation pit engineering; then knowledge of active earth pressure on piles is very important for engineers. In this paper, based on the pseudodynamic method and considering the vehicle’s vibration characteristic, a method to calculate the earth pressure on piles under vehicle load is presented. At the same time, the constraint of anchor is simplified relation of lateral deformation of piles in present method. Effects of a wide range of parameters like rupture angle, vibration acceleration coefficient, wall friction angle, and soil friction angle on active earth pressure have been studied. Results are presented in terms of coefficients in the figures and comparison of the test data and the earth pressure calculated by M-O method and present study. The result shows that the measured earth pressure is accordant with the theoretical analysis, so the method in this paper is an effective basis for the calculation of earth pressure on piles under vehicle loads.